Analysis of cutting stock problem metaheuristic algorithms - Pokštas, Jonas; Listopadskis, Narimantas (Lietuvos matematikos rinkinys, 2021)
The analysis of cutting stock problem and heuristic and metaheuristic algorithms for solving it are presented in this paper.